Success of passive and active restoration of lowland hay meadows with regard to current and historical references - Dellicour, Maïké; Goret, Thibaut; Piqueray, Julien; Fayolle, Adeline; Bindelle, Jérôme; Mahy, Grégory (Frontiers in Ecology and Evolution, 2023)
The restoration of hay meadows is one of the major challenges in temperate Europe, to overcome the drastic loss and degradation of these semi-natural habitats. Evaluation of restoration success requires the definition of a relevant reference ecosystem. Historical phytosociological relevés dating from the 1960s-1970s, before large scale agriculture intensification, may be used as the reference framework for such purposes. However, this reference framework may no longer be pertinent in our present-day ecological and socio-economic context. In this study, we assessed the success of three restoration techniques for lowland hay meadows, based on plant species richness and composition and functional traits, by comparing the restoration trajectories to historical and current references. The three restoration techniques, passive restoration mowing, active fresh hay transfer and active sowing of threshing material, were implemented depending on the initial level of degradation and the proximity to well-preserved meadows. The species composition of restored meadows clearly differed from historical references but converged toward current references, for both passive and active restoration techniques. Historical references are characterized by short, stress-tolerant dicotyledonous plant species with small specific leaf area: indicators of nutrient-poor environments. The gap observed between plant communities of historical and current meadows suggests that the historical data are an over-ambitious target for restoration purposes and can hardly be considered relevant to our present-day context. Therefore, creation of a new reference framework of lowland hay meadows is needed for the adequate implementation of restoration projects. Successful outcomes of active and passive techniques must encourage practitioners to adapt the choice of the restoration method depending on the local ecological context, i.e., level of degradation and proximity to well-preserved habitats.